2022
DOI: 10.1039/d1me00154j
|View full text |Cite
|
Sign up to set email alerts
|

Bayesian optimization for material discovery processes with noise

Abstract: An augmented Bayesian optimization approach is presented for materials discovery with noisy and unreliable measurements. A challenging non-Gaussian, non-sub-Gaussian noise process is used as a case study for the discovery...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…Process optimization using ML techniques has the advantages of rapidly assessing and screening a large number of parameters and iteratively converging to optimal decisions. 48,49 A popular approach used in the scientific community research is active learning, a subfield of AI, and have been demonstrated in virtual materials discovery, [50][51][52][53] synthesis, 54,55 and electrochemical performance testings. 49 In this section, we review two case studies, where active learning techniques were applied to optimize device fabrication and device operation, respectively.…”
Section: Optimizing Processesmentioning
confidence: 99%
“…Process optimization using ML techniques has the advantages of rapidly assessing and screening a large number of parameters and iteratively converging to optimal decisions. 48,49 A popular approach used in the scientific community research is active learning, a subfield of AI, and have been demonstrated in virtual materials discovery, [50][51][52][53] synthesis, 54,55 and electrochemical performance testings. 49 In this section, we review two case studies, where active learning techniques were applied to optimize device fabrication and device operation, respectively.…”
Section: Optimizing Processesmentioning
confidence: 99%
“…Moreover, Diwale et al presented an augmented BO method to overcome the noise issues in either experiments or simulations. 102…”
Section: Fundamentalsmentioning
confidence: 99%
“…In most materials design scenarios, the acquisition function is of less importance, where most studies employed the expected improvement and/or upper (lower) condence bound. [100][101][102][103] However, the evaluation of the objective, i.e. the mapping X / y, is of key interest in most cases applying BO for materials design.…”
Section: Variational Autoencoders (Vae)mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the tedious process of eliminating internal and external mass transfer and determining residence time limits the efficiency and accuracy of kinetic modeling. In addition, experimental results of heterogeneous catalysis often come with noise introduced by temperature, barometric pressure, and other environmental factors, which may lead to lower search efficiency and convergence properties in the optimization 19 . Our previously developed MOBO platform 20 used NEHVI, a MOBO acquisition function for hypervolume maximization in both noisy and noise-free environments 21 , but the comparison of different acquisition functions in terms of their ability to handle noise has not been systematically studied.…”
Section: Introductionmentioning
confidence: 99%